Relationships between Health Promoting Activities, Life Satisfaction, and Depressive Symptoms in Unemployed Individuals - Chatzisarantis, Nikos; Kamarova, Sviatlana; Twomey, Chris; Hansen, G.; Harris, Mark; Windus, J.; Bateson, A.; Hagger, Martin (HOGREFE PUBLISHING CORP, 2021)
Background: Previous research has documented that unemployed individuals who engage in recreational activities, either alone or with others, experience higher levels of mental health and psychological well-being relative to those who do not engage in recreational activities. Aims: In this study, we examined whether engagement in health promoting activities, alone or with other family members, is associated with reduced levels of depression and enhanced levels of life satisfaction in unemployed individuals.